Effects of Cd addition to NiTi shape memory alloys on thermal, mechanical and corrosion behaviour - Balci, Esra; Tatar, Cengiz; Tatar, Beyhan; Dagdelen, Fethi (Indian Acad Sciences, 2024)
In this study, it is aimed to investigate the effects of NiTiCd alloy, which is formed by adding Cd element to NiTi shape memory alloys, on some physical and chemical parameters. The chemical compositions (% atomic) of the produced alloys were prepared as Ni48Ti50Cd2 and Ni46Ti50Cd4. Some thermodynamic parameters of these samples were investigated by DSC, structural analysis by SEM-EDX and XRD, hardness by Vickers microhardness method and corrosion behaviour by electrochemical method. The thermal activation energy required for phase transformations of alloys was calculated using the Kissinger and Ozawa methods. The average thermal activation energies obtained from the two methods are 85.76 kJ mol-1 for Ni48Ti50Cd2 SMA and 106.93 kJ mol-1 for Ni46Ti50Cd4 SMA. The XRD and SEM-EDX analyses indicated that the Ti element was the dominant constituent in the precipitate microstructures. It was found that with an increasing amount of cadmium, the microhardness of NiTi alloy decreases. It was calculated that Ni46Ti50Cd4 SMA has the best corrosion resistance compared to Ni48Ti50Cd2 alloys in terms of corrosion analysis.
Keywords: Shape memory alloys; NiTiCd; thermal activation energy; microstructure; microhardness; corrosion resistance